Islam-West Relations: Clash or Cooperation? - L. Salman Al-Farisi (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
The theme of Islam-West relations in this paper explores several findings from academic studies, utilizing a literary study approach aimed at elucidating the 'roots' of conflict and the factors influencing the occurrence of conflict in Islam-West relations. Findings from an in-depth analysis of several current literatures describe the historicity and the impact analysis of the Crusades as the root of the issues underlying the confrontation and clash (conflict) in Islam-West relations. Furthermore, the most influential factors in shaping Western stereotypes of Islam are attributed to misunderstandings in the application of the 'sacred concept' of democracy and the interpretation of the 'evil doctrine' of Jihad, as well as the mention of